The Use of Importance-Performance Analysis to Evaluate Quality of Service Provided by UNMC Information Services Centre - Kanji, Arif (2009)
Purpose – This study aims to evaluate the services provided by Information Services (IS) department to its internal customers using the Important-Performance Analysis (IPA) tool to improve its services in an effective and efficient manner. Design/methodology/approach – A mixed method of qualitative interviews with the four IS staff members as well as the nine customers of the IS department from the Faculty of Engineering, Science and Social Science was conducted, and an online survey for customers was also conducted. Findings – The modified Importance-Performance Analysis model is an extremely useful tool, which assists IS managers to best deploy their resources to achieve the highest degree of customer satisfaction. Research & Limitations – The limitations was on the research being conducted in the three faculties only. The IPA tool proved to be useful in directing the IS manager to allocate his resources to maximize customer satisfaction. Originality/value – This paper offers a powerful, easy to use yet cost effective way for any IS manager to satisfy their internal customers within any sector by studying the service providers as well as the customers. Keywords – Customer Satisfaction, Importance-Performance Analysis, Information Services (IS) Paper type – Dissertation paper